Monitoring of training and racing of long distance runners using heart rate monitors - Mbambo, Ziphelele Hazlitt (MRC/UCT RU for Exercise and Sport Medicine, 2018)
Aim: The aim of this thesis was to contribute to a better understanding of heart rate during exercise with the aim of improving the precision with which heart rate can be used to measure intensity during running. Accordingly, heart rate responses were examined in long distance runners during different types of training and racing. The thesis also examined the effects of environmental and body temperature on heart rate during submaximal and maximal running. Study 1: Ten male provincial and national class road runners (VO₂max = 67.1 ± 3.8 mlO₂.kg⁻¹. min⁻¹) were recruited for the study. All the subjects completed questionnaires on their training history and recorded their training sessions in their diaries. The subjects wore heart rate monitors during training and racing. There was no convincing evidence that competitive runners who train at higher intensities have a better running performance. A poor relationship was found between %VO₂max and %HRmax. Finally, heart rate during races was higher compared to heart rates during training. The cause of the elevated heart rate during races was not clear. Study 2: The relationship between heart rate and running speed during competition was not well understood. Accordingly, an elite long distance male runner (25 years, VO₂max = 71 mlO₂.kg⁻¹. min⁻¹) was studied over a 5-month period during which time he participated in 9 races (5 km - 28 km). The subject wore a heart rate monitor which measured his heart rate throughout the race and his split running times each kilometre. The subject underwent a field test during which the heart rate/running speed relationship was determined under non-competitive conditions (r = 0.99). However, in the race situation there was no relationship between heart rate and running speed (r = 0.02). It was concluded that during competition there was no relationship between heart rate and running speed, whereas in a non-competitive situation heart rate was proportional to running intensity. Study 3: With a poor relationship found between heart rate and running speed during races in the previous study, other factors like environmental conditions and core temperature were hypothesised to have effects on heart rate. Accordingly, twelve highly trained distance runners were recruited for the study. Each subject ran on a treadmill (30 minutes at 70% peak treadmill running speed, followed by 8 km time trial) in different ambient temperatures (15°C, 25°C and 35°C) with humidity (60%) and wind speed (15 km.h⁻¹) kept constant. Heart rate, RPE and Tre were recorded every 5 minutes during the submaximal and the maximal trials. When subjects were exercising at 70% of peak treadmill running speed at 15°C, no cardiovascular drift was observed, at least for 30 minutes. However, during the same exercise test at 25 °C and 35°C there was a significant increase in heart rate. In the maximal exercise test the average heart rate was significantly higher during the trial at 35°C compared to the trials at 15° C and 25° C. It was concluded that heart rate can be used as an accurate measure of running intensity in cooler (15 ° C) ambient temperature. In summary, this thesis described the practical use of heart rate monitors during training and competition and at different temperatures. Data are provided which suggest that heart rate can accurately assess exercise intensity providing factors which affect the heart rate/running speed relationship are controlled.